Kantian empirical cognition and singular concepts - Özdağ, Cenk. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
The subject-matter of this thesis is the distinction between empirical intuitions and empirical concepts in terms of two criteria, namely the singularity criterion and the immediacy criterion. The goal of the thesis on this issue is to show that these two criteria are distinct and independent from each other and one of them cannot be reduced to other. For reaching this goal and to provide a clearer account of these criteria, the two criteria are redefined to solve the problems that emerge in various interpretations of them in literature. It is argued that intuitions too are mediate but their mediacy is different from that of concepts. It is claimed that the difference between empirical intuitions and empirical concepts depend on the analysis of empirical cognition by abstracting concepts from empirical cognition in order to find an element that provide the conditions of existence of logically possible objects. The distinction between concepts and intuitions is related with the contemporary debate on nonconceptual content. In this thesis, it is argued that there is nonconceptual content in empirical cognition, but it is possible to think that the nonconceptual content other than spatiotemporal relations could be provided by sensations with the collaboration of concepts. Another fundamental goal of this thesis is to find a way to speak of singular concepts within the Kantian corpus that is compatible with the central tenets of Kantian philosophy and to provide a ground to give examples of the singular use of concepts. In the thesis, it is shown that both the singular use of concepts and singular concepts are compatible with the Kantian account of concepts.
Keywords: Intuition -- Philosophy.; Concepts.